Adorno and Horkheimer’s Diagnosis of Modernity - Wonicki, Rafał (Sensus Historiae, 2022)
The aim of the article is to show that the first generation of the Frankfurt School - mostly Adorno and Horkheimer - created a critical theory as a tool for the diagnosis of a modern way of understanding rationality and social relations. Positivism has disappointed expectations with regard to the understanding of social power relations. While analyzing the Enlightenment’s reason, which fell into instrumentalisation and mythologization, and which is able to - on the basis of its own thinking - overcome its weaknesses, the Frankfurters want again to rebuild social ties that are not based on violence.